MANAJEMEN TERAPI ISLAM DAN PROSEDUR PELAYANANNYA - Alang, Sattu (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2020)
Therapeutic therapy is a process to cure someone of a disease they experience, both psychological and mental illness which is done by experts. Therapy must be done regularly, well-programmed and repeatedly for the purpose of improving themselves to become healthier and get a better life. better. In the medical field, the word therapy is the same as the word treatment. The process of Islamic therapy in healing through an Islamic approach which is often referred to as Istisfa ’. Islamic therapy must go through several stages, namely: Begin with an initial interview about what will happen during therapy. The next procedure the therapist (counsellor) needs to study and explore the experience of the client, explore past experiences as long as it is relevant to the problems faced by the client. The next action, both the therapist and the client, reexamines what the client has learned during therapy, and what he will apply later in his life. And finally, therapy can end if the goal has been agreed, but it can also end if the client does not continue therapy.